Where to put your best foot forward: Psycho-physiological responses to walking in natural and urban environments. (March 2016) - Gidlow, Christopher J.; Jones, Marc V.; Hurst, Gemma; Masterson, Daniel; Clark-Carter, David; Tarvainen, Mika P.; Smith, Graham; Nieuwenhuijsen, Mark
Abstract: There is convergent evidence that natural environments allow restoration from stress. This randomised, cross-over, field-based trial compared psychological and physiological responses of unstressed individuals to self-paced 30-min walks in three pleasant environments: residential (urban), natural (green), and natural with water (blue). Changes from baseline (T1) to T2 (end of 30-min walk), and T3 (30 min after leaving environment) were measured in terms of mood, cognitive function, restoration experiences, salivary cortisol, and heart rate variability (HRV). In the final sample (n = 38; 65% male; mean age 40.9 ± 17.6 years), mood and cortisol improved at T2 and T3 in all environments. Green and blue environments were associated with greater restoration experiences, and cognitive function improvements that persisted at T3. Stress reduction (mood and cortisol changes) in all environments points to the salutogenic effect of walking, but natural environments conferred additional cognitive benefits lasting at least 30 min after leaving the environment. Graphical abstract: Highlights: Non-stressed adults walked in natural (with/without water) and pleasant urban environments. Mood improved in natural and urban environments. Salivary cortisol reduced in natural and urban environments. Restorative experience was higher in natural environments. Greater cognitive benefits of natural environments were seen 30 min after leaving the environment.